From less promising to green? Technological opportunities and their role in (green) ICT innovation - Grazia Cecere; Sascha Rexhäuser; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper aims to shed light on the role of technological opportunities for green innovation by studying the case of Green ICT innovation. We test two hypotheses: (1) Firms active in low-opportunity technological areas are less innovative; (2) Firms active in low-opportunity technological areas are more likely to change their direction of technical change. To do so, we construct a firm-level panel data set for the years 1992-2009 combining patent data from the European Patent Office with firm-level data from the German Innovation Panel (Mannheim Innovation Panel). The results are based on dynamic count data estimation models applying General Methods of Moments estimators. Our results support our hypotheses: firms active in low-opportunity technological areas are less innovative but are more likely to switch from pure ICT innovation to Green ICT innovation.
urn:nbn:de:bsz:180-madoc-405258
Keywords: 330; technological opportunities; innovation; information and communication technology (ICT); green ICT; firm-level patent data; dynamic count data model